Electrocatalytic Activity of Nanohybrids Based on Carbon Nanomaterials and Mfe2o4 (M=Co, Mn) Towards the Reduction of Hydrogen Peroxide - Zagal-Moya, J; Zagal-Moya, J (Wiley-VCH Verlag, 2018)
We report the advantages of hybrid nanomaterials prepared with electrogenerated ferrites (MFe2O4; M: Co, Mn) and multi-walled carbon nanotubes (MWCNTs) or thermally reduced graphene oxide (TRGO) on the electro-reduction of hydrogen peroxide. Glassy carbon electrodes (GCE) modified with these hybrid nanomaterials dispersed in Nafion/isopropanol demonstrated a clear synergism on the catalytic reduction of reduction of hydrogen peroxide at pH 13.00. The intimate interaction between MFe2O4 and carbon nanomaterials allowed a better electronic transfer and a facilitated regeneration of M2+ at the carbon nanomaterials, reducing the charge transfer resistances for hydrogen peroxide reduction and increasing the sensitivities of the amperometric response. © 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim